The Analysis Of Quality Product And Price Perception Towards Purchase Decisions (Survey On 'Bakmi Boerangrang Tasikmalaya' Consumers) - Erika Joanna Hosea; Depy Muhamad Pauzy; Mila Karmila (Penerbit Jurnal Indonesia, 2023)
The purposes of this study was to determine the effect of quality product and price perception towards purchase decision of 'Bakmi Boerangrang Tasikmalaya'. This study used quantitative method and survey from 100 respondents from 'Bakmi Boerangrang' consumers. The type of data used is multiple regression analysis. The result of the study showed that quality product and price perception have a significant effect either partially or simultaneously towards purchase decision of 'Bakmi Boerangrang Tasikmalaya' consumers.